Dlaczego Owidiusz? Postmodernistyczne biografie alternatywne wielkiego poety - Gawarecka, Anna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Article analyses a literary portrait of Publius Ovidius Naso in the novels Naso the Poet (1969) by Jacek Bocheński, An Inexplicable Story or the Narrative of Questus Firmus Siculus by Josef Škvorecky (1998) and The Last World. A Novel with an Ovidian Repertory by Christoph Ransmayr (1988).